Dehydrocrenatidine inhibits head and neck cancer cells invasion and migration by modulating JNK1/2 and ERK1/2 pathway and decreases MMP‐2 expression. Issue 9 (2nd June 2021) - Velmurugan, Bharath Kumar; Lin, Jen‐Tsun; Mahalakshmi, B.; Lin, Chia‐Chieh; Chuang, Yi‐Ching; Lo, Yu‐Sheng; Ho, Hsin‐Yu; Hsieh, Ming‐Ju; Chen, Mu‐Kuan
Abstract: Head and neck cancer is associated with poor prognosis because of its highly metastatic nature. For the better management of head and neck cancer patients, it is very important to diagnose the cancer at an early stage, as well as to prevent the rapid spread of cancer either through direct invasion or lymphatic metastasis. In present study, the effect of dehydrocrenatidine, which is a beta‐carboline alkaloid found in the medicinal plant Picrasma quassioides, on human head and neck cancer metastasis was investigated. The study results revealed the treatment of FaDu, SCC9, and SCC47 cells with 5, 10, and 20 μM of dehydrocrenatidine significantly decreased the motility, migration, and invasion of head and neck cancer cells. Moreover, the dehydrocrenatidine treatment significantly decreased the expression of MMP‐2 and phosphorylation of ERK1/2 and JNK1/2. Additional experiments revealed that the cotreatment of dehydrocrenatidine with either ERK1/2 or JNK1/2 inhibitor caused further reduction in cancer cell motility and migration compared to that in dehydrocrenatidine treatment alone. Moreover, similar trend was observed in case of ERK1/2 and JNK1/2 phosphorylation and MMP‐2 expression after the cotreatment. Taken together, the mechanism by which dehydrocrenatidine can decrease the phosphorylation of ERK1/2 and JNK1/2, follow decrease the expression of MMP‐2 and inhibits head and neck cancer cells invasion and migration. This present study identifies dehydrocrenatidine as a potent antimetastatic agent that can be used clinically to improve head and neck cancer prognosis.